RISK MANAGEMENT OF TELKOM INFRASTRUCTURE ASSURANCE UNIT BANDUNG - Rahmat Sentiko, Fajar
Entering the era of Industry 4.0, Indonesia must prepare various aspects to be able to compete in the international environment accompanied by the rapid development of technology such as the Internet of Things, Artificial Intelligence, and The use of Big Data. To support the government program, PT Telkom Indonesia precisely the Infrastructure Assurance (IAS) unit has an active role in the development of infrastructure that supports the industrial revolution 4.0 precisely in the telecommunications sector. To maintain service quality and prioritize customer satisfaction, companies must follow ISO rules as guidelines for carrying out their business activities. In this case, IAS Telkom Bandung must follow ISO 17025: 2017 which contains General Requirements for Competence in Testing and Calibration Laboratories with a risk-based thinking approach. Because of the urgent need for implementation of ISO 17025: 2017, Komite Akreditasi Nasional (KAN) requires that IAS has its own risk management. Therefore, the IAS unit must conduct risk assessments and implement risk management to improve performance and anticipate risks that can disrupt the stability of the company's business. The concept used is the adoption of the risk management process issued by ISO 31000: 2009 which contains the scope, definition, principles, framework, and also the risk management process. External analysis uses Porter five forces to analyze industry attractiveness, while external environment analysis uses Political, Economic, Sociocultural, Technological analysis. Internal analysis uses analysis of resources and capabilities. From external and internal analysis, the company can know the strengths, weaknesses, opportunities, and threats (SWOT) that the company has that can be used to identify risks that might occur. The risk identification process is carried out from various sources including, SWOT Analysis, Interviews and Brainstorming with Experts, and other research. Next is to do a risk analysis using Analytical Hierarchy Process (AHP). AHP is done using Business Performance Management Singapore (BPMSG) Online Software by calculating level 1 to level 3, which then searches for their respective weights, then after obtaining the results of risk evaluation by mapping the risks of these risks. The final step is risk mitigation by making a classification based on 4 mitigations. In general, the mitigation action is Accept, Avoid, Reduce, and Transfer. Based on the results of the risk analysis, there are 29 risk factors from 7 different types of risks, namely Business, Environmental, Financial, Legal, Market, Operational and Reputation risks. Risks that have a critical level of risk are 1 risk, risks that have a high risk level are 15 risks, and risks that have a moderate risk level of 8 risks and those with a low risk level are 5 risks. Of the 29 risk factors possessed, the risks made by further mitigation plans are 16 risks. These risks are 1 risk that has a level of critical risk, and 15 risks that have a high risk. The implementation plan is made to implement the strategy using Person in Charge (PIC), budgeting plans, and schedules in order to reduce likelihood and the impact caused by these risks.